2013
DOI: 10.2528/pierc13011709
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method of Node and Threshold Selection in Wavelet Packet Transform for Uwb Impulse Radio Signal Denoising

Abstract: Ultra wide band (UWB) impulse radio (IR) technology has different applications in different sectors such as short range radios and collision avoidance radar. A strong signal denoising method is needed for UWB-IR signal detection. One of the challenges of UWB-IR signal detection technique is the environmental interferences and noises. Wavelet Packet Transform (WPT) based multi-resolution analysis technique is suitable for this kind of signal denoising and detection. The paper describes a better method of denois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They also published papers presenting the use of Wavelet Packet Transform (WPT) [7], generalization of the DWT, for noise suppression and subsequent PD extraction [8][9][10]: their analysis, however, was limited only to numerical signals. WPT has also been used recently for UWB impulse radio signal denoising [11], although the authors do not comment on possible limitations and drawback of the adopted technique. Satish and Nazneen [12] used the DWT for extracting PD pulses buried in very high levels of noise and interferences and showed that the results obtained with the proposed wavelet-based denoising technique were superior with respect to those obtained with different digital filtering approaches, such as the FIR (Finite Impulse Response) method and the IIR (Infinite Impulse Response)-notch filter method.…”
mentioning
confidence: 99%
“…They also published papers presenting the use of Wavelet Packet Transform (WPT) [7], generalization of the DWT, for noise suppression and subsequent PD extraction [8][9][10]: their analysis, however, was limited only to numerical signals. WPT has also been used recently for UWB impulse radio signal denoising [11], although the authors do not comment on possible limitations and drawback of the adopted technique. Satish and Nazneen [12] used the DWT for extracting PD pulses buried in very high levels of noise and interferences and showed that the results obtained with the proposed wavelet-based denoising technique were superior with respect to those obtained with different digital filtering approaches, such as the FIR (Finite Impulse Response) method and the IIR (Infinite Impulse Response)-notch filter method.…”
mentioning
confidence: 99%